Can routinely collected data be used to reliably follow-up participants in large randomised trials? - Harper, C (2023)
Background Large randomised controlled trials (RCTs) in cardiovascular disease have provided reliable evidence for interventions whose widespread use has contributed to the secular declines in mortality. But, increasing costs of conducting RCTs threaten our ability to generate new randomised evidence. Linkage to health data collected during a person’s routine care (i.e. routine data) has the potential to substantially streamline trial follow-up, however, there remains considerable uncertainty about the reliability of such information.